1998
DOI: 10.1104/pp.116.1.419
|View full text |Cite
|
Sign up to set email alerts
|

Three 1-Aminocyclopropane-1-Carboxylate Synthase Genes Regulated by Primary and Secondary Pollination Signals in Orchid Flowers1

Abstract: The temporal and spatial expression patterns of three 1-aminocyclopropane-1-carboxylate (ACC) synthase genes were investigated in pollinated orchid (Phalaenopsis spp.) flowers. Pollination signals initiate a cascade of development events in multiple floral organs, including the induction of ethylene biosynthesis, which coordinates several postpollination developmental responses. The initiation and propagation of ethylene biosynthesis is regulated by the coordinated expression of three distinct ACC synthase gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
56
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(62 citation statements)
references
References 38 publications
4
56
0
2
Order By: Relevance
“…A comparison between tissue and time-course expression allowed us to determine that 78% (1,066) of the regulated transcripts were first expressed before pollination in UP or unfertilized ovules, 7% (96) were exclusively induced by pollination (absent in any other tissue directly involved in the reproductive process), 12% (170) represent transcripts identified initially as preferentially expressed in our pollen data set (absent from UP or ovules), and 3% (36) were enriched (Supplemental File S2). Despite the predominant expression of genes in the pistil at receptivity, only a few proteins expressed in the sporophytic female tissues were identified with functions in pollen-pistil interactions (Wu et al, 2000;de Graaf et al, 2003;Palanivelu et al, 2003;Park and Lord, 2003), and only one gene was identified to be strictly induced by pollination (Bui and O'Neill, 1998). The comparison of our time-course data set with recently reported transcriptomes of in vitro (Wang et al, 2008) and semi-in vitro pollen tube growth (Qin et al, 2009) confirmed an expected overlap of multiple genes "de novo" transcribed during pollen tube growth and possibly induced due to interactions with the female tissues.…”
Section: Gene Regulation Underlying the Progamic Phasementioning
confidence: 99%
“…A comparison between tissue and time-course expression allowed us to determine that 78% (1,066) of the regulated transcripts were first expressed before pollination in UP or unfertilized ovules, 7% (96) were exclusively induced by pollination (absent in any other tissue directly involved in the reproductive process), 12% (170) represent transcripts identified initially as preferentially expressed in our pollen data set (absent from UP or ovules), and 3% (36) were enriched (Supplemental File S2). Despite the predominant expression of genes in the pistil at receptivity, only a few proteins expressed in the sporophytic female tissues were identified with functions in pollen-pistil interactions (Wu et al, 2000;de Graaf et al, 2003;Palanivelu et al, 2003;Park and Lord, 2003), and only one gene was identified to be strictly induced by pollination (Bui and O'Neill, 1998). The comparison of our time-course data set with recently reported transcriptomes of in vitro (Wang et al, 2008) and semi-in vitro pollen tube growth (Qin et al, 2009) confirmed an expected overlap of multiple genes "de novo" transcribed during pollen tube growth and possibly induced due to interactions with the female tissues.…”
Section: Gene Regulation Underlying the Progamic Phasementioning
confidence: 99%
“…Four of the ACC synthase genes in tomato have been shown to be differentially regulated in fruit and hypocotyls during ripening by wounding and auxin treatment . ACC synthase mRNAs are also induced during flower senescence and following pollination in carnation and orchid Woodson et al, 1992;O'Neill et al, 1993;Jones and Woodson, 1997;Bui and O'Neill, 1998). Few studies of other species have included the investigation of ACC synthase expression in floral tissue.…”
mentioning
confidence: 99%
“…Highly divergent ACC synthase multigene families have been identified and characterized in Arabidopsis (Liang et al, 1992(Liang et al, , 1996; Van der Straeten et al, 1992), tomato (Olson et al, 1991;Rottmann et al, 1991;Yip et al, 1992;Lincoln et al, 1993;Oetiker et al, 1997), mung bean (Botella et al, 1992a(Botella et al, , 1992b(Botella et al, , 1993Kim et al, 1992Kim et al, , 1997, zucchini (Huang et al, 1991), rice (Zarembinski and Theologis, 1993), potato (Destefano-Beltran et al, 1995;Schlagnhaufer et al, 1995), and orchid (Bui and O'Neill, 1998). The Arabidopsis gene family includes at least five members whose expression is differentially induced by hormones, developmental cues, Li ϩ , and the protein-synthesis inhibitor CHX (Liang et al, 1996).…”
mentioning
confidence: 99%
“…13,14 Moreover, auxin up-regulated the ethylene biosythethic genes in Phalaenopsis, Phal-ACS2 and Phal-ACS3, and auxin-induced ethylene production was secondarily enhanced through ethylene-stimulated Phal-ACS1 expression. 30 Independent of ethylene, auxin treatment depressed transcript levels of the Phalaenopsis gene, PeMADS6, whose function is to sustain the life of the floral parts while inhibiting the completion of ovary and ovule maturation after pollination. 32 However, both auxin and ethylene response elements have been identified in the promoter region of PeMADS6, implicating both hormones in this pollination-induced shift in gene expression.…”
mentioning
confidence: 99%
“…13,14,29 Most of these changes are mediated through auxin-stimulated ethylene production. [29][30][31] In fact, a combination of auxin and ethylene are needed for optimal ovary/ovule development. The addition of ethylene antagonists to pollinated or unpollinated, NAA-treated stigmas resulted in partial stigmatal closure and moderate ovary swelling, and only a small amount of perianth senescence, while ethylene alone promoted death of the perianth without ovary enlargement or closure of the stigma.…”
mentioning
confidence: 99%